2015
DOI: 10.18632/oncotarget.3528
|View full text |Cite
|
Sign up to set email alerts
|

FKBPL: a marker of good prognosis in breast cancer

Abstract: FK506-binding protein-like (FKBPL) has established roles as an anti-tumor protein, with a therapeutic peptide based on this protein, ALM201, shortly entering phase I/II clinical trials. Here, we evaluated FKBPL's prognostic ability in primary breast cancer tissue, represented on tissue microarrays (TMA) from 3277 women recruited into five independent retrospective studies, using immunohistochemistry (IHC). In a meta-analysis, FKBPL levels were a significant predictor of BCSS; low FKBPL levels indicated poorer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…To date, the mechanism of action has been attributed to a potential role in the CD44 pathway and stabilisation of p21 [5,22,36]. In addition to this, we have shown that high FKBPL levels are associated with a positive prognosis in breast cancer [21]. In this study, for the first time, we assessed the pre-clinical activity of novel systemic anti-cancer therapeutic peptides, ALM201 & AD-01, in the metastatic setting, and highlighted their impact on endocrine therapy resistant cancer stem cells; both areas of unmet clinical need.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…To date, the mechanism of action has been attributed to a potential role in the CD44 pathway and stabilisation of p21 [5,22,36]. In addition to this, we have shown that high FKBPL levels are associated with a positive prognosis in breast cancer [21]. In this study, for the first time, we assessed the pre-clinical activity of novel systemic anti-cancer therapeutic peptides, ALM201 & AD-01, in the metastatic setting, and highlighted their impact on endocrine therapy resistant cancer stem cells; both areas of unmet clinical need.…”
Section: Discussionmentioning
confidence: 69%
“…Intracellular FKBPL regulates ER signalling and, as such, has prognostic value in terms of breast cancer survival. This was demonstrated using publically available datasets [21] and in a meta-analysis of five independent breast tissue microarray (TMA) cohorts [21,22]. In this cohort of 3277 patients, FKBPL was a significant and independent predictor of breast cancer specific survival (BCSS), with low FKBPL expression being associated with shorter BCSS (HR = 1.31, 95% CI 1.15-1.50, p < 0.001).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this study, we demonstrated that expression of the key proteins in placental angiogenesis, FKBPL, SIRT-1, PlGF and VEGFR-1, 27,30,[45][46][47] is dysregulated in pregnancies complicated by diabetes. The FKBPL's role in diabetic pregnancies has never been demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%